Modelagem e Simulação de uma Microrrede Piloto Isolada Com Provimento de Referência Através de um Gerador Síncrono Virtual - Basoni, Renan Corrêa (2017)
This dissertation proposes the provision of voltage and frequency reference for isolated microgridsthrough a virtual inertia control strategy for inverters.The control strategy proposed in this dissertation to establish reference to an isolated microgrid is implemented using a virtual synchronous machine, for that, an inverter that mimics the behaviorof synchronous machines, also known as Synchronverter, will be utilized. A microgrid is defined as the aggregation of distributed generations, loads and energy storagesystemsthat work in a coordinated way.The microgrid has the capacity to operate isolated from the utility grid, for that, it must be capable of creating its own reference of voltageand frequency.Normally, in this circumstance, the voltage reference for the synchronization and connectionof other sources is provided by synchronous generators moved by internal combustion machines, which has some disadvantages, such as the production of noise, emission of harmful gases, consumption of fossil fuel, etc. The proposal in thisdissertationis an alternative to the use of these generators, using a battery energy storage system, frequency inverter, DC-DC bidirectional buck-boost quadratic converter and an appropriate control. The amplitude of voltage and frequency must be controlled according to the power quality standards for urban consumers.Thisdissertationpresents a modeling made on EMTDC/PSCAD of a microgrid including local loads, battery storage, DC-DCconverters, power inverters, wind turbine and a solar array located at Universidade Federal do Espírito Santo -BR. The results prove the efficiency of the adopted control, keeping the voltage and frequency of the grid controlledduring load changes, as well as the electrical energy balance delivered to the system by the photovoltaic and wind generator sources.